PP2A and Its Inhibitors in Helper T-Cell Differentiation and Autoimmunity - Khan, Mohd Moin; Kalim, Ubaid Ullah; Khan, Meraj H.; Lahesmaa, Riitta (Frontiers in Immunology, 2022)
Protein phosphatase 2A (PP2A) is a highly complex heterotrimeric Ser/Thr phosphatase that regulates many cellular processes. The role of PP2A as a tumour suppressor has been extensively studied and reviewed. However, emerging evidence suggests PP2A constrains inflammatory responses and is important in autoimmune and neuroinflammatory diseases. Here, we review the existing literature on the role of PP2A in T-cell differentiation and autoimmunity. We will also discuss the modulation of PP2A activity by endogenous inhibitors and its small-molecule activators as potential therapeutic approaches against autoimmunity.